Предмет: Алгебра,
автор: Alexander2121322
Упростите алгебраическое выражение
А) 3а-(2а-(а-7))
Б) 6d-(3d-((k-8d) -2k))
Ответы
Автор ответа:
0
A) 3a - ( 2a - ( a - 7 )) = 3a - ( 2a - a + 7 ) = 3a - a - 7 = 2a - 7
Б) 6d - ( 3d - (( k - 8d ) - 2k ) = 6d - ( 3d - k + 8d - 2k ) = 6d - ( 11d - 3k ) = 6d - 11d + 3k = 3k - 5d
Б) 6d - ( 3d - (( k - 8d ) - 2k ) = 6d - ( 3d - k + 8d - 2k ) = 6d - ( 11d - 3k ) = 6d - 11d + 3k = 3k - 5d
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: saibulaevaslan
Предмет: Математика,
автор: danilsedlar75
Предмет: Математика,
автор: Илюшо
Предмет: Алгебра,
автор: ASIA1111